PENGARUH STRUKTUR MODAL, KEBIJAKAN DIVIDEN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERDAGANGAN BESAR BARANG PRODUKSI YANG TERDAFTAR DI BEI - Fatimatuz Zehro; Ika Wahyuni; Febri Ariyantiningsih (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The objective of this study was to determine the effect of capital structure, dividend policy, and firm size on firm value, with financial performance as an intervening variable in Wholesale Manufacturing Companies Listed on the Indonesia Stock Exchange. The sampling technique used in this study was simple random sampling of 98 consumers. Data analysis and hypothesis testing in this study used the Partial Least Squares Structural Equation Model (PLS-SEM). The results showed that capital structure had a significant positive effect on financial performance, dividend policy had a significant positive effect on financial performance, firm size had a significant negative effect on financial performance, capital structure had a positive but insignificant effect on firm value, dividend policy had a positive but insignificant effect on firm value, firm size had a positive but insignificant effect on financial performance, financial performance had a significant positive effect on firm value, capital structure had a significant positive effect on firm value through financial performance, dividend policy had a significant positive effect on firm value through financial performance, and firm size had a significant negative effect on firm value through financial performance. Financial.